2017
DOI: 10.31219/osf.io/9ungq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Act versus Impact: Conservatives and liberals exhibit different structural emphases in moral judgment

Abstract: Conservatives and liberals disagree sharply on matters of morality and public policy. We propose a novel account of the psychological basis of these differences. Specifically, we find that conservatives tend to emphasize the intrinsic value of actions during moral judgment, in part by mentally simulating themselves performing those actions, while liberals instead emphasize the value of the expected outcomes of the action. We then demonstrate that a structural emphasis on actions is linked to the condemnation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 31 publications
6
17
1
Order By: Relevance
“…Additionally, people are consciously aware of this emotional arousal when they contemplate personal moral dilemmas and report being more aroused on self-report measures (Szekely & Miu, 2014). Although this evidence corroborates the role of reduced negative affect in utilitarian moral judgements, a more nuanced analysis is in order because negative affect can derive from two different psychological mechanisms, namely outcome and action aversion which respectively stem from victim and agent perspective-taking (Cushman, Gray, Gaffey, & Mendes, 2012;Hannikainen, Miller, & Cushman, 2015;Miller, Hannikainen, & Cushman, 2014). Therefore, it needs to be determined which of these sources are responsible for reduced negative affect that underlies increased utilitarian tendencies.…”
Section: Reduced Negative Affect and Utilitarian Moral Judgementsmentioning
confidence: 55%
See 3 more Smart Citations
“…Additionally, people are consciously aware of this emotional arousal when they contemplate personal moral dilemmas and report being more aroused on self-report measures (Szekely & Miu, 2014). Although this evidence corroborates the role of reduced negative affect in utilitarian moral judgements, a more nuanced analysis is in order because negative affect can derive from two different psychological mechanisms, namely outcome and action aversion which respectively stem from victim and agent perspective-taking (Cushman, Gray, Gaffey, & Mendes, 2012;Hannikainen, Miller, & Cushman, 2015;Miller, Hannikainen, & Cushman, 2014). Therefore, it needs to be determined which of these sources are responsible for reduced negative affect that underlies increased utilitarian tendencies.…”
Section: Reduced Negative Affect and Utilitarian Moral Judgementsmentioning
confidence: 55%
“…At first blush, it might seem surprising that outcome aversion did not predict utilitarian moral judgements on either impersonal or personal moral dilemma. But, as argued by others (Hannikainen et al, 2015;Miller et al, 2014) who have observed similar patterns of responses, this is probably due to the idiosyncratic nature of moral dilemmas where both action and omission produce bad outcomes. Since harmful outcome would materialise for either the distal (the five people that need to be saved) or the proximal (the one person that needs to be sacrificed) victim/s irrespective of the choice the agent makes, outcome aversion would not preferentially recommend either alternative.…”
Section: Two Sources Of Negative Affect In Moral Judgementmentioning
confidence: 76%
See 2 more Smart Citations
“…If someone attempts to betray their in-group, but is unsuccessful in their act of betrayal, does that make the attempted betrayal any less immoral? There is some evidence to support the possibility that the action of betrayal is more relevant than the outcome of betrayal in moral judgments (Hannikainen, Miller, & Cushman, 2017), along with evidence that people have a strong "betrayal aversion" (Bohnet, Greig, Herrmann, & Zechhauser, 2008) that leads them to judge acts of betrayal more harshly than harmful acts with identical outcomes but no aspect of betrayal (Koehler & Gershoff, 2003). From this evidence, we can infer a tentative hypothesis: The level of experiential mind perception attributed to the victim of a loyalty violation is less relevant to judgments of wrongness than it is to judgments to wrongness in the harm and fairness domains (because these domains typically have clearer victims).…”
Section: Using Social Influence To Inform Debates In Moral Cognitionmentioning
confidence: 99%